Vpliv programov predpristopne pomoči EU na razvoj obmejnih območij Slovenije v obdobju 1994-2004 - Piry, Ivo (Dela - Oddelek za geografijo Filozofske fakultete v Ljubljani, 2006)
Article reviews some elements of development process if border areas of Slovenia as regards influences of pre-accession programme Phare cross-border co-operation (Phare CBC). Republic of Slovenia received Phare assistance from 1992 onwards. Regional development of slovene border areas was closely related to the geopolitical situation and function of border areas. After 1994 it was included also in the programme of cross border co-operation Phare CBC. It was aimed at fighting regional differences of border areas that were neglected as regards investments and remained most peripheral areas of the country.
Keywords: Slovenia; Slovenija; obmejna območja; regionalni razvoj; razvojna strategija; razvojni programi; European Union; Evropska unija